ANTIBATERIAL ACTIVITY OF (HERICIUM ERINACEUS) EXTRACT ON SOME CLINICAL PATHOGENIC ISOLATES - M. S. Khalaf; M. S. Shawkat (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The purpose of this research was to find the effect of alcoholic extract of the lion’s mane mushroom (Hericium erinaceus) against certain clinical pathological isolates isolated from Iraqi patients suffering from various diseases such as gingivitis, urinary tract infection, diarrhea and severe vomiting, and also a biopsy was taken from the stomach of people suffering from ulcers. Out of 150 males and females sample 107 samples were isolated and identified by chemical detection and VITEK 2 technique, and by PCR for Halicobacter pylori as follows: Staph aureus(56),Salmonella typhi(6),Pseudomonas aeruginosa(10),Escherichia coli(15),Halicobacter pylori(10),Klebsiella pneumonia(10),Candida albicans(10) samples. lion’s mane mushroom powder was extracted with 80% ethyl alcohol, and active components were investigated by chemical reagents and Gc-mass. The chemical detection of Alcoholic extract revealed the existence of flavonoids, alkaloids, phenols, terpenoids, glycosides, and polysaccharides. The efficacy of the extract was tested using 4 concentrations (400, 200, 100, and 50 mg/ml) on bacterial and yeast isolate (C.albicans).The diameter of the inhibitory zone increased with increasing extract concentrations, according to the findings. Zone of inhibition for all isolates started at 100mg/ml except C.albicans(50mg/ml)and E.coli (200mg/ml)